2017
DOI: 10.3389/fnbeh.2017.00054
|View full text |Cite
|
Sign up to set email alerts
|

Non-Interfering Effects of Active Post-Encoding Tasks on Episodic Memory Consolidation in Humans

Abstract: So far, studies that investigated interference effects of post-learning processes on episodic memory consolidation in humans have used tasks involving only complex and meaningful information. Such tasks require reallocation of general or encoding-specific resources away from consolidation-relevant activities. The possibility that interference can be elicited using a task that heavily taxes our limited brain resources, but has low semantic and hippocampal related long-term memory processing demands, has never b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
61
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(75 citation statements)
references
References 43 publications
10
61
4
Order By: Relevance
“…These findings stand in contrast to a number of previous studies investigating the resting effect under different experimental conditions (Brokaw et al 2016;Cowan et al 2004;Craig et al 2014Craig et al , 2015Della Sala et al 2005;Dewar et al 2009Dewar et al , 2012aMercer 2015), but support the results of recent studies, which showed that resting is no prerequisite for successful memory consolidation (e.g. Varma et al 2017). In the following, we address possible arguments for our findings.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…These findings stand in contrast to a number of previous studies investigating the resting effect under different experimental conditions (Brokaw et al 2016;Cowan et al 2004;Craig et al 2014Craig et al , 2015Della Sala et al 2005;Dewar et al 2009Dewar et al , 2012aMercer 2015), but support the results of recent studies, which showed that resting is no prerequisite for successful memory consolidation (e.g. Varma et al 2017). In the following, we address possible arguments for our findings.…”
Section: Discussioncontrasting
confidence: 57%
“…Dewar et al 2007Dewar et al , 2012a. The results of Experiment 1 did not support this view, but showed that post-learning wakeful rest was no prerequisite for successful memory consolidation (see also Varma et al 2017). In Experiment 2, we tested whether the visual distractor task might have modulated our findings in Experiment 1.…”
Section: Methodsmentioning
confidence: 56%
See 3 more Smart Citations